Pengaruh Kecanduan Konten Digital Pendek terhadap Kemampuan Konsentrasi Mahasiswa Calon Guru Ekonomi - Yuniyarti Ahiri; Jafar Ahiri; Muh. Ilham; Murni Nia; Rizal (Educational Journal, 2026)
Concentration ability is crucial for pre-service economics teacher students to master complex economic concepts and develop pedagogical competencies. This study examines the impact of short-form digital content addiction on students' concentration abilities. A quantitative correlational research design was employed, involving 180 students from the Economics Education Department, Faculty of Teacher Training and Education, Halu Oleo University, selected through proportionate stratified random sampling. Data were collected using the Short-Form Video Addiction Scale questionnaire and the Grid Concentration Test. Simple linear regression analysis revealed that short-form digital content addiction had a significant negative effect on concentration ability (p=0.000<α=0.05), with the regression equation Y = 23.418 - 0.132X. The path coefficient of -0.552 indicates that short-form digital content addiction has a negative effect (-55.2%) on students' concentration ability. The findings demonstrate that higher levels of addiction to TikTok, Instagram Reels, and YouTube Shorts correspond to lower concentration ability among students.